2016
DOI: 10.1111/tmi.12816
|View full text |Cite
|
Sign up to set email alerts
|

Retention in care and reasons for discontinuation of lifelong antiretroviral therapy in a cohort of Cameroonian pregnant and breastfeeding HIV‐positive women initiating ‘Option B+’ in the South West Region

Abstract: We observed good uptake of HTC, ART and retention in care, which declined over time. Discontinuation of Option B+ was highest at small sites with a high staff turnover. Improved staffing, adequate task shifting and community interventions to track defaulters including reducing stigma and religious beliefs may improve Option B+ retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 26 publications
2
52
2
1
Order By: Relevance
“…Attention needs to be paid to continuing the support and training of healthcare workers so that retention can be maintained and improved . In Cameroon (Option B+), retention rates of 88% were noted at 6 months, with decreases in retention over time which are much higher than the retention rates found in this study.…”
Section: Discussioncontrasting
confidence: 84%
“…Attention needs to be paid to continuing the support and training of healthcare workers so that retention can be maintained and improved . In Cameroon (Option B+), retention rates of 88% were noted at 6 months, with decreases in retention over time which are much higher than the retention rates found in this study.…”
Section: Discussioncontrasting
confidence: 84%
“…The uptake of PMTCT procedures in our study was very good with a loss of follow‐up rate of 4.9%, which is less than reported in other studies . The majority of women in our study were HIV diagnosed and started ART during pregnancy within a median duration of 1.3 weeks between HIV diagnosis and ART initiation, 46.4% of women started treatment within 1 week after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although this apparently did not lead to high mother‐to‐child transmission rates, it may raise concern on treatment durability and development of drug resistance as reported in pregnant women from South Africa and Malawi . Evidence for poor post‐partum treatment adherence was also seen in our analysis, as the proportion of women with self‐reported poor adherence was significantly higher during the post‐partum period than before delivery. Poor self‐reported adherence was significantly associated with women who started ART very late during the perinatal period, indicating that enforced adherence counselling after delivery is especially needed in these women.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the presence of efforts, loss to Follow-up (LTFU) and poor adherence to drugs are still a major challenge to achieve virtual elimination of MTCT of HIV especially in Sub-Saharan Africa (12).…”
mentioning
confidence: 99%
“…Another retrospective cohort study in Myanmar showed that pregnant women's LTFU rate was 7 per 1000 person-years under option B+ PMTCT programs (11). A retrospective follow-up study in different African countries showed that the incidence of LTFU among pregnant and lactating mothers under option B+ program were still high which ranges from 16% to 53.7 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Previous studies in Ethiopia showed that the rate of LTFU among women under Option B+ program varied region to region.…”
mentioning
confidence: 99%